Skrining Pencegahan Penularan TBC (SiGaP-TBC) di Pondok Pesantren Hidayatulloh Al-Muhajirin, Bangkalan - Salim, Hotimah Masdan; Mulyadi, Mulyadi; Prasetya, Dwi Arman (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2025)
Pondok Pesantren Hidayatullah Al-Muhajjirin accommodates approximately 500 male and female students aged 14 to 18, offering education at the Madrasah Tsanawiyah and vocational high school (SMK) levels. Given the diverse backgrounds of these students, their awareness of Clean and Healthy Living Behavior (PHBS) varies, impacting efforts to prevent airborne diseases like tuberculosis (TB). To address this, a community service initiative introduced the SiGaP-TBC program, aiming to enhance knowledge about TB transmission and promote self-screening. Methods included educational sessions, health screenings, utilization of the SiGaP-TBC application for self-assessment, and training in food self-sufficiency through healthy gardening. The program led to increased student awareness of PHBS in TB prevention, the establishment of student health cadres within the pesantren's health management system, and improved self-screening capabilities using the SiGaP-TBC app. In conclusion, the SiGaP-TBC program effectively fosters self-reliance in TB infection prevention and health empowerment within the pesantren community.